2005
DOI: 10.1515/jpem.2005.18.2.171
|View full text |Cite
|
Sign up to set email alerts
|

Constitutional Delay of Growth and Puberty: From Presentation to Final Height

Abstract: This retrospective study evaluated clinical characteristics of patients with constitutional delay of growth and puberty (CDGP) at presentation, during puberty and at final height. The records of 151 children (105 boys, 46 girls) with CDGP were reviewed and the results were evaluated with respect to findings in healthy Turkish schoolchildren. CDGP was twice as frequent in boys as in girls. Height and weight deficit and short sitting height of the children were evident at presentation and continued up to final h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 16 publications
3
33
1
1
Order By: Relevance
“…CDGP constitutes a fairly large group of patients seen in pediatric clinics [11, 14-16] with boys presenting much more frequently than girls [9, 11, 14, 17]. No indices for adult height prediction are available for boys with retarded bone ages >13 years in the BP method [2].…”
Section: Introductionmentioning
confidence: 99%
“…CDGP constitutes a fairly large group of patients seen in pediatric clinics [11, 14-16] with boys presenting much more frequently than girls [9, 11, 14, 17]. No indices for adult height prediction are available for boys with retarded bone ages >13 years in the BP method [2].…”
Section: Introductionmentioning
confidence: 99%
“…In 1993, Albanese and Stanhope [10] investigated 34 girls, in whom adult stature was as much as 1.5 SDS below TH. Of 46 girls studied by Poyrazoglu et al [28] in 2005, 76% did not reach their parental TH range. These numbers are in accordance with our results.…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, only a few studies have reported AH in girls with this condition [1,7,10,28], probably because of the paucity of girls with CDGP seen in clinical practice. Although AH in girls with CDGP has been stated to be within a normal range of the general population [7], it may remain below the genetic target [1,10,28]. In the study by Crowne et al [1] in 1991, AH in 23 female CDGP subjects was 0.7 SDS below their TH [1].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of CGDP was defined as [10] height below the third percentile or > 2 standard deviation (SD) below that of children of the same chronological age and sex, according to center for disease control (CDC) clinical growth charts based reference, delayed bone age (by ≥ 2 years), low growth rates < 5 cm/y, GH response of > 10 µg/L to at least two stimulation tests (clonidine and exerciseinduced) in otherwise healthy prepubertal boys. Systemic or specific causes of short stature were ruled out by history, physical examination and routine laboratory tests.…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…The use of clonidine in children with CGDP has been the subject of several studies [8,9] but, very divergent results have been reported and therefore the effectiveness of clonidine in increasing growth rate of CGDP is not clear. Many subjects affected by constitutional short stature show a good response to human growth hormone (HGH) therapy, whereas others do not benefit by this treatment [10][11][12][13]. The use of aromatase inhibitors and oxandrolone, a weak anabolic steroid has been shown to be effective in children with CGDP.…”
Section: Introductionmentioning
confidence: 99%